Accounting and finance regulations by state Islamic religious council and Waqf, Zakat and Baitulmal Institutions in Malaysia - Ishak, Suhaimi; Ku Ismail, Ku Nor Izah; Derashid, Chek; Abu Bakar, Fathiyyah; Sawandi, Norfaiezah; Abdul Wahab, Muhammad Syahir (2019)
This paper discusses legislation adopted by the State Islamic Religious Council (MAIN) and the waqf, zakat and baitulmal institutions (WZB), particularly in relation to accounting and finance. The study involved only the states of Perlis, Kedah, Penang, Perak and Sarawak. The Federal Constitution, the Statutory Bodies (Accounts and Annual Reports) Act 1980 (Act 240), and several Acts relating to this topic are discussed. Meanwhile, the Administration of Islamic Religious Administration and the Ordinance of each state was also examined to discuss this. The data was obtained through interviews with accountants or financial officers of MAIN and WZB institutions. In addition, research on important documents such as the ACT, financial regulations and annual reports of MAIN and WZB institutions was also undertaken. The results of this study have provided a new input into the legal knowledge used by MAIN and the WZB institutions in accounting and finance. Finally, the findings of this study have also been an important input in the formulation of Islamic accounting standards by the Accounting Department of Malaysia (JANM).